Islamic Leadership Narratives on YouTube: A Framing Analysis of Digital Da’wah Messages - Nasution, Nadya Amalia; Alisya (Ath Thariq Jurnal Dakwah dan Komunikasi, 2024)
This research aims to analyze the framing of da’wah messages on YouTube, focusing on leadership themes. Using a constructionist approach through Robert N. Entman's framing model, this study examines four elements: define problems, diagnose causes, make moral judgments, and make treatment recommendations. The research analyzes four YouTube videos uploaded between September 2022 and September 2023, each having more than 1,000 views and containing leadership-themed da’wah content. The findings reveal that the da’wah messages are categorized into three types: faith-based messages (found in videos 1 and 3), sharia-based messages (found in videos 2 and 4), and moral-based messages (found in video 4). The framing analysis identifies consistent patterns in highlighting leadership aspects through four perspectives: defining leadership issues in religious contexts, identifying systemic causes of leadership problems, emphasizing moral judgments based on Islamic values, and recommending solutions that combine religious teachings with leadership practices. This study concludes that the da’wah messages frame leadership issues by presenting specific viewpoints to the public, emphasizing the importance of integrating Islamic principles in leadership while addressing current social and governmental concerns.